Assessing the effects of artificial light at night on biodiversity across latitude – Current knowledge gaps. Issue 3 (22nd November 2019) - Secondi, Jean; Davranche, Aurélie; Théry, Marc; Mondy, Nathalie; Lengagne, Thierry
Abstract: Aim: Exposure to artificial light at night (ALAN) is a risk factor for organisms. Considering the spread and increasing intensity of night brightness across the globe, and the key role of light at all biological levels, alterations of ecosystems are expected. Yet, we cannot predict the severity of the effects of ALAN in several biomes because little information is available outside the temperate zone. We reviewed current knowledge and identified traits that could be targeted to fill this knowledge gap in order to contribute to the elaboration of a biogeographical framework for the study of ALAN at the global scale. Location: Global. Time period: Current and next decades. Methods: We analysed the latitudinal variation in ALAN and focused on environmental factors that vary with latitude but that have been overlooked. We reviewed biological traits that exhibit latitudinal variation and depend on light and photoperiod and compiled information about the predicted changes in human demography and road networks across different world regions. Results: Cloud cover amplifies ALAN far away from urbanized areas. Because of the higher frequency of overcast sky nights, exposure effects may be stronger both at high latitudes and across a large fraction of the intertropical zone, although at different times of the year. Intertropical biomes host the largest fraction of global biodiversity. Although currently they are not the most exposed to ALAN, their human populations are growing, and urbanized areas and road networks are expanding. Hence, ALAN could have strong ecological consequences, with cloud cover as an aggravating factor. Perspectives: Knowledge gaps currently limit our ability to predict the effects of ALAN in different biomes. Therefore, it will be important to start investigating the consequences of this novel environmental factor across the globe, in order to develop a relevant theoretical framework.